1993
DOI: 10.1088/2058-7058/6/5/24
|View full text |Cite
|
Sign up to set email alerts
|

The atom as microscopic undulator

Abstract: Electrons emit electromagnetic radiation when they are accelerated. When an electron moves through a macroscopic magnetic field the acceleration is caused by the Lorentz force and the radiation is called synchrotron radiation. If, on the other hand, the electron is accelerated by the microscopic Coulomb (electric) field of a nucleus, the associated radiation is called bremsstrahlung. In general both types of radiation are incoherent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…The identical preparation of excited states from an initially pure state in these experiments, with conservation of reflection symmetry about the scattering plane, leads to a state which can be described by a single state vector [20) +a_2(O,E) 12-2 ) (1) where aM(O, E) are the angle and energy dependent scattering amplitudes associated with the excited [LM) states. The a ± ~ associated with the 12 ± 1) states are zero because these states have negative reflection symmetry about the scattering plane.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…The identical preparation of excited states from an initially pure state in these experiments, with conservation of reflection symmetry about the scattering plane, leads to a state which can be described by a single state vector [20) +a_2(O,E) 12-2 ) (1) where aM(O, E) are the angle and energy dependent scattering amplitudes associated with the excited [LM) states. The a ± ~ associated with the 12 ± 1) states are zero because these states have negative reflection symmetry about the scattering plane.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In this report we are interested in the latter case. van Linden van den Heuvell et al [1,2] discussed the theory of Dstate correlation studies in helium and performed a novel scattered electron-cascade photon angular correlation experiment. However, substantial quantitative studies of 3 1D excitation were first reported by Beijers et al [3] using the polarisation correlation technique in which the linear and circular polarisations of the emitted (31D -21p) dipole radiation were determined.…”
Section: Introductionmentioning
confidence: 99%
“…Previous attempts to investigate the polarization properties of the *On leave from: Fakult~it ffir Physik, Universit/it BieIefeld, D-33501 Bielefeld, Germany emitted light during the decay of collisionally excited He (3 1D) states have mostly been restricted to measurements [5][6][7][8][9] perpendicular to the scattering plane which is defined by the directions of the incoming and outgoing electron. The information obtained from such measurements yielding the so-called Stokes parameters Pi (i = 1-3) is, however, incomplete and at least one more (in-plane) measurement (P4) is needed to extract the full information accessible by such measurements.…”
Section: Introductionmentioning
confidence: 99%
“…The essential physics behind such phenomena is often described by the classical simpleman's model, in which the electron is assumed to be created in a flat potential and gains energy from or loses it to the low frequency field. The simpleman's model was originally developed to describe above threshold ionization (ATI) [4][5][6], and it is an excellent approximation in cases in which there is high frequency excitation far above the ionization limit or very strong low frequency fields [1,[7][8][9]. In these terms the excitation of He occurs at an IR phase such that the He electron gains energy from the IR field.…”
mentioning
confidence: 99%